Monitoring the changes of a suburban settlement by remote sensing - LÁSZLÓ NAGYVÁRADI; PÉTER GYENIZSE; ANITA SZEBÉNYI (Acta Geographica Debrecina. Landscape & Environment Series)
Satellite images and aerial photos support settlement surveys and provide valuable information of their physical environment. Aerial photos are excellent tools to overview large areas and simultaneously provide high-resolution images making them efficient tools to monitor built-up areas and their surroundings. Aerial photos can also be used to collect complex spatial data as well as to detect various temporal changes on the land surface, such as construction of illegal edifices and waste dumps. The 10 to 30-meter resolution SPOT and Landsat images are usually insufficient for site specific data collection and analysis. However, the recently available 0.5-meter resolution satellite images have broadened the scope of monitoring and data collection projects. Beyond environmental and urban monitoring, the new available high-resolution satellite images simplify the everyday work of local authorities and will facilitate the development of governmental databases that include spatial information for public utilities and other communal facilities.